Outcomes of assisted reproductive technologies in discordant couples with HIV infection in a woman - Helen V. Mituyrina; Svetlana G. Perminova; Elena S. Sannikova (IP Berlin A.V., 2023)
Aim. To evaluate the effectiveness of assisted reproductive technologies (art) in discordant couples with hiv-infected women. Materials and methods. The prospective clinical study included 432 women who received an in vitro fertilization (ivf) program. The main group included 214 subjects with hiv infection, and the control group included 218 subjects without hiv infection. In the main group, 182 "fresh" ivf/icsi (intracytoplasmic sperm injection) cycles and 162 cryocycles were performed; in the control group, 271 and 195 cycles, respectively. Results. The median length of HIV infection was 9.8 (5.7; 12.4) years, subclinical stage 3 of the disease prevailed (59.8%), and the duration of antiretroviral therapy was 4.5 (2.4; 8) years. The CD4+lymphocyte count [630 (496; 791) cells/μL] indicated a relatively "good" state of the immune system due to the antiretroviral therapy. In the main group, a significantly lower number of oocyte-cumulus complexes [6.5 (3; 12) and 9 (6; 15); p0.001], zygotes [4 (2; 8) and 6 (4; 10); p0.001] and blastocysts [2 (0; 2) and 4 (1; 6); p0.001] were obtained in comparison with the control group. The number of abnormally fertilized oocytes (3 or more PNs) was significantly higher in the group of HIV-infected women compared to HIV-negative ones - 0.21 (0.7) and 0.09 (0.2) (p=0.018), respectively. Evaluation of the effectiveness of "fresh" IVF/ICSI cycles showed that HIV-infected women had a significantly lower incidence of clinical pregnancy (16.5 and 32.8%; p=0.001), as well as live births (12.2 and 31.5%; p0.001). Analysis of cryocycle outcomes showed that using their own oocytes in women with HIV infection, the frequency of clinical pregnancy (27.6 and 41%; p=0.014) and childbirth (16.7 and 27.7%; p=0.021) is significantly lower than in patients without HIV infection, and in cases of using donor oocytes, these indicators are comparable between the groups (40%; p=0.910 and 25.7%; p=0.809, respectively). Conclusion. ART in HIV-infected women is associated with low pregnancy rates in both "fresh" and cryocycles using their own oocytes. The decrease in the oocytes/embryos obtained and the high proportion of abnormal fertilization in HIV-infected patients suggest the presence of oocyte factor as the main cause of the low effectiveness of ART programs in this group of patients.